Sistemas de manejo de solo em áreas irrigadas por pivô central - Hauschild, Fabio Evandro Grub (2019)
The management of the irrigation in fields under no-till system was established according to the water potential in the soil as limiting factor to plant growth. However, the physical and chemical of the soil subsurface, such as the compaction and the distribution of nutrients in the soil rooting layer, may also limit the growth, and consequently, the crop yield, regardless of the water potential was inside the interval corresponding to the water available. In this context, the aim of this study was investigate the effect of the chemical and physical improvement of the rooting zone of the soil, by the use of gypsum (G), limestone (C), cover crops (PC) and chiseling (ESC) isolated and combined in the soybean and maize grain yields, and too realize an economic analysis identifying the strategies of management with more profitability. The experiment was conducted in a commercial field in a Typic Hapludox. The experimental design followed a trifactorial scheme, with the principal parcel constituted by the management system, the subparcel by the use of PC and the subsubparcel by the application of C and/or G. The use of PC in SPD, in relation to ESC was effect similar in the mitigation penetration resistance (values). The combination of the ESC and PC presented the lower PR values in the final of the experimental period. The use of ESC+PC+C+G was effect in the soil layer of 0-35 cm in relation to SPD, increasing this attribute to more of 5,5 until the 15 cm depth. However, the SPD+PC+C+G presented intermediary behavior, with limited effect in the layer of 15 cm. The higher increases in the soil depth of the calcium (Ca2+) e magnesium (Mg2+) contents were observed in the treatments submitted to C and G application combined with highlight to treatment submitted to ESC. The combination of the treatments to three crop seasons increase significantly the grain yield of the crops, with the higher values to treatment ESC+PC+C+G and lower to control. The soybean seed yield in the treatment ESC+C+G not presented statistical difference to three crop seasons in relation to SPD+PC+C+G, indicating that the utilization of PC associated with C and G application in SPD it’s an efficient alternative to increase the grain yield without the need for soil tillage with the chiseling. The use of cover crops associated with the chiseling presented economic return faster in relation to other treatments. The integrated strategies of soil management provided higher economic return accumulated in relation to isolated use of these strategies. The isolated use of the chiseling, although of the low cost of implantation, presented in the lower economic return, identified as an inefficient management. However, with the combination of the chiseling with cover crops, limestone and gypsum was the better strategy to increase the crop yield and economic return.